EFFECTIVENESS NATIONAL HEALTH INSURANCE (JKN) USING MOBILE APPLICATION TO PATIENTS BPJS HEALTH SERVICES IN SIBOLGA CITY - Herlina, Benri Situmorang; Herlina, Herlina (Bajang Institute, 2024)
The National Health Insurance (JKN) mobile application is a form of digital transformation of the BPJS business model that can be used by participants anywhere and at any time without time limits for convenience for BPJS users and the public. The convenience in question includes paying BPJS fees, changing membership data, knowing participant family data. Research objective: to find out the use of the National Health Insurance (JKN) application to increase the effectiveness of BPJS health services in Sibolga. This type of research is descriptive research with a qualitative approach. This research took four sources as sources. Meanwhile, data collection techniques use observation, interview and documentation techniques. The research results show that the effectiveness of BPJS health services through the National Health Insurance (JKN) mobile application in the city of Sibolga is said to be effective and efficient because this application really helps administrative activities at the BPJS health office in serving the community. The JKN mobile application is very helpful for accessing BPJS health services because of the many features in it so that participants do not need to go to the BPJS health office, by using the JKN mobile application or care center participants can immediately get BPJS health services